Planning for a Landing Operation of the Polish People’s Army on the Danish Isles during the Cold War - Pałka, Jarosław (Kwartalnik Historyczny, 2023)
During the Cold War, the Polish People’s Army (hereinafter: PPA) planned to occupy Denmark, the northern regions of the Federal Republic of Germany, the Netherlands and Belgium through an offensive campaign. An essential element of this scheme was air and seaborne landing operations aimed at capturing the Danish island of Zealand and the country’s capital, Copenhagen. The actions undertaken by the PPA were intended to comprise part of a large-scale campaign of the allied forces of member states of the Warsaw Pact against NATO. In the mid-1980s, the landing tasks of the PPA were limited to the occupation of the Danish island of Bornholm.